1997
DOI: 10.1002/(sici)1096-8628(19971212)73:2<127::aid-ajmg5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Private multiple congenital anomaly syndromes may result from unbalanced subtle translocations: t(2q;4p) explains the Lambotte syndrome

Abstract: In 1990, Lambotte syndrome was reported as an apparently autosomal recessive multiple congenital anomaly/mental retardation (MCA/MR) syndrome observed in 4 of 12 sibs from a probably consanguineous mating [Verloes et al., Am J Med Genet 1990; 37:119-123]. Major manifestations included intrauterine growth retardation (IUGR), microcephaly, large soft pinnae, hypertelorism, beaked nose, and extremely severe neurologic impairment, with holoprosencephaly in one instance. After the observation of a further affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…This observation confirms previous reports that small chromosomal aberrations, difficult to detect by standard cytogenetic techniques, may cause familial ‘private’ syndromes, especially those where transmission occurs through unaffected individuals and where multiple miscarriages are present [4,5].…”
supporting
confidence: 91%
“…This observation confirms previous reports that small chromosomal aberrations, difficult to detect by standard cytogenetic techniques, may cause familial ‘private’ syndromes, especially those where transmission occurs through unaffected individuals and where multiple miscarriages are present [4,5].…”
supporting
confidence: 91%
“…Some of those cases were previously published and accepted as bona fide Mendelian phenotypes: Lambotte syndrome (case 10; Verloes et al 1990;Herens et al 1997), GOMBO syndrome (case 11; Verloes et al 1989Verloes et al , 2000 or Haspeslagh syndrome (Haspelslagh et al 1985;Devriendt et al 2000). Screening for telomeres in patients with de novo visible aberrations was also shown to detect familial rearrangements and more precisely define de novo aberrations: Kashork et al (1999), studying 32 patients with a visible "de novo" del(1p36), showed that the apparently terminal 1p deletion resulted from a cryptic rearrangement in five cases (three with 1qter; each one with 2pter and Xpter) and was an interstitial deletion in five other cases.…”
Section: Discussionmentioning
confidence: 99%
“…The family was initially reported as having an autosomal recessive malformation syndrome (Verloes et al 1990). The discovery of the familial unbalanced rearrangement lead to an update (Herens et al 1997). …”
Section: Familial Translocationsmentioning
confidence: 99%
“…All were the unbalanced products of inherited translocations or inversions, and the trisomic segment varied less than in the cases of isolated duplications. In some cases, the monosomic segment contributed substantially to the phenotype [Ardinger et al, 1987;Herens et al, 1997], and in other cases, the deletion was thought to be miniscule and unimportant to the phenotype [Rosenthal et al, 1974;Warren et al, 1975;Zabel et al, 1976;Cotlier et al, 1977;Angle et al, 2000]. Not surprisingly, growth retardation was more common in cases with accompanying deletions.…”
Section: Discussionmentioning
confidence: 99%